Surrogate motherhood contract. The US American experience (2012)
The article has the purpose of identifying and presenting the United States experience regarding the contract on surrogate motherhood. This experience has the following main features: a) there is a regulation of the contract founded in the law and case law, b) there is no uniform position among the states regarding the legal enforceability of the contract, c) public policy and family law are used to determine the legal validity of the agreement, and d) the regulation of the contract is directed to counter the negative effects of contract. Likewise, the article wants to identify the common points between the U.?s vision and the Colombian.